2012
DOI: 10.1111/ijfs.12042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial replacement of potassium lactate and sodium diacetate by natural green tea and grape seed extracts and postpackaging thermal treatment on the growth of Listeria monocytogenes in hotdog model system

Abstract: Low-(5%) and high-fat (20%) chicken and turkey hotdogs were formulated in three groups: no antimicrobials (control), chemical preservatives (potassium lactate and sodium diacetate) alone and partial replacement of chemical preservatives by green tea (GTE) and grape seed extracts (GSE), surface inoculated (c. 10 3 CFU g À1 ) with Listeria monocytogenes, treated with or without heat treatment (65°C for 104 s) to determine the growth of L. monocytogenes until spoilage (28 days). Maximum growth inhibitions (c. 2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Maximum growth inhibition (∼2.0 log CFU/g) of L. monocytogenes was observed in chicken and turkey hot dogs treated with combinations of potassium lactate and sodium diacetate with green tea and grape seed extracts. The antilisterial effect was enhanced by heat treatment of the hot dogs, suggesting that the extracts can partially replace the chemical preservatives and enhance the antilisterial activities …”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…Maximum growth inhibition (∼2.0 log CFU/g) of L. monocytogenes was observed in chicken and turkey hot dogs treated with combinations of potassium lactate and sodium diacetate with green tea and grape seed extracts. The antilisterial effect was enhanced by heat treatment of the hot dogs, suggesting that the extracts can partially replace the chemical preservatives and enhance the antilisterial activities …”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…(Monroy, 2007;Sasse et al, 2009 andKulkarni et al, 2011). In addition, grape seed extract exhibited antibacterial activity (Baydar et al, 2006;Over et al, 2009;Sagdic et al, 2011 andPerumalla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate the potential of thyme and oregano EOs to inhibit bacterial growth in food products whit high protein contents (10%–12.5% SPI) and a pH range from 5.5 to 6.5. Perumalla et al (2013) demonstrated that a combination of potassium lactate (3.00%) and sodium diacetate (0.15% or 0.20%), utilized as ingredients in the formulation of hotdog model systems, was able to inhibit L. monocytogenes growth; their blends achieved growth inhibitions of 3.4 and 2.4 Log CFU/g on the 16th and 21st days of storage, respectively, in the case of chicken hotdog samples, and of 3.2 and 1.6 Log CFU/g on the 16th and 21st days of storage, respectively, for turkey hotdog samples.…”
Section: Resultsmentioning
confidence: 99%